Geological Study of Soil Quality Degradation in Jharkhand and Its Management - Dr. Krishna Gopal (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Soil quality degradation is a significant environmental concern in Jharkhand, India, a region rich in mineral resources and diverse geological formations. The degradation of soil in this area is influenced by both natural geological processes and human activities, such as mining, agriculture, and deforestation. This study aims to explore the geological factors contributing to soil degradation and propose management strategies tailored to the region's unique geological context. The geological diversity of Jharkhand, which includes sedimentary, metamorphic, and igneous rock formations, plays a crucial role in shaping soil properties such as texture, fertility, and erosion susceptibility. This study examines the relationship between soil quality and geological factors such as mineral composition, weathering, erosion, and sedimentation. It highlights how these processes, when exacerbated by human intervention, lead to nutrient depletion, soil erosion, and the loss of soil fertility, thus reducing agricultural productivity. The findings suggest that soil management in Jharkhand must incorporate a geological perspective to address the specific challenges posed by the region’s geological setting. The research advocates for geologically informed soil conservation practices, such as terracing, erosion control, and the use of locally appropriate soil amendments. The study emphasizes the importance of sustainable land management programs, including afforestation and community-driven conservation efforts.
Keywords: Geological Study; Soil Quality; Soil Degradation; Jharkhand